Cross-Sectional Study of the Relation of Health Literacy to Primary Language and Emergency Department Length of Stay. Issue 12 (December 2017) - Sarangarm, Dusadee; Ernst, Amy; Horner, Rachel; Crum, Ashley; Weiss, Steven J.; Zemkova, Yana; King, Kisa
Abstract : Objectives: The primary aim of this study was to determine whether emergency department (ED) length of stay (LOS) or primary language was related to the degree of health literacy of patients. Methods: Adult English-speaking and Spanish-speaking patients were recruited for the study. Participants completed the Newest Vital Sign (NVS) tool (English and Spanish versions), a 6-question validated scale. Patients with NVS scores of 0 to 3 were considered to be at risk for limited health literacy, whereas those with adequate health literacy were defined as scoring a 4 to 6. After completion of their ED visit, a retrospective chart review was performed to identify the patient's ED LOS (time from registration to time of disposition) and ED disposition. In addition, 2 single-item questions were compared with the NVS for validity. Results: Participants included 250 English-speaking and 257 Spanish-speaking subjects. Per the NVS, 71% (359 of 507) of all patients had limited health literacy. By language group, significantly more Spanish-speaking than English-speaking patients had limited health literacy (93% vs 48%, diff 45%, 95% confidence interval 37–51). There was no significant difference in LOS between the limited health literacy group and adequate health literacy group (medians 440 vs 461 min). The 2 single-item questions had fair validity in comparison to the NVS scale (κ 0.2–0.3). Conclusions: There was a significant difference in health literacy based on language, with 93% of all Spanish-speaking patients in our sample having limited health literacy. We found no significant difference in ED LOS between patients with limited health and adequate health literacy in an academic urban ED setting. Abstract : This was a cross-sectional survey of emergency department patients, examining their degree of health literacy as measured by a validated health literacy scale, the Newest Vital Sign. The authors compared health literacy between Spanish-speaking and English-speaking patients and completed a multivariable analysis looking for predictors of health literacy. In addition, the authors investigated whether a single question could substitute for the Newest Vital Sign scale.